The Biomarker Potential of Caveolin-1 in Penile Cancer - Panic, Andrej; Reis, Henning; Wittka, Alina; Darr, Christopher; Hadaschik, Boris; Jendrossek, Verena; Klein, Diana (Frontiers in Oncology, 2021)
Various types of human cancers were characterized by an altered expression of epithelial or stromal caveolin-1 (CAV1). However, the clinical significance of CAV1 expression in penile cancer remains largely unknown. Here the expression pattern of CAV1 were analyzed in a retrospective cohort (n=43) of penile squamous cell carcinoma. Upon penile cancer progression, significantly increased CAV1-levels were determined within the malignant epithelium, whereas within the tumor stroma, namely the fibroblastic tumor compartment harboring activated and/or cancer associated fibroblasts, CAV1 levels significantly decline. Concerning the clinicopathological significance of CAV1 expression in penile cancer as well as respective epithelial-stromal CAV1 distributions, high expression within the tumor cells as well as low expression of CAV1 within the stromal compartment were correlated with decreased overall survival of penile cancer patients. Herein, CAV1 expressions and distributions at advanced penile cancer stages were independent of the immunohistochemically proven tumor protein p53 status. In contrast, less differentiated p16-positive tumor epithelia (indicative for human papilloma virus infection) were characterized by significantly decreased CAV1 levels. Conclusively, we provide further and new evidence that the characteristic shift in stromal‐epithelial CAV1 being functionally relevant to tumor progression even occurs in penile SCC.